Checklist of Fishes at Pergau Lake, Jeli, Kelantan, Malaysia - Malisa Ilyana Mohd Alias; Kamarul Hambali; Aainaa Amir; Norashikin Fauzi,; Hizami Hassin; Sow Ai Yin (Tropical Life Sciences Research, 2019)
A survey was conducted to determine the diversity of fish in Pergau Lake, Jeli, Kelantan, Malaysia from 2 September to 18 October of 2016. Fish samples were collected at seven random sampling stations around the lake by using setting trap method. The collected samples were preserved in 10% formalin solution and delivered to the laboratory for further identification process. Fourteen species, namely as Hemibagrus nemurus, Hampala macrolepidota, Clarias batrachus, Channa striata, Cyprinus carpio, Poropuntius smedleyi, Pangasius sp., Oreochromis niloticus, Oreochromis mossambicus, Leptobarbus hoevenii, Neolissochilus hexagonolepis, Tor tambroides, Osteochilus hasselti and Neolissochilus soroides, comprising of six families were collected during this study. From this study, family of Cyprinidae was the dominant species in Pergau Lake with exactly 50% of catch percentage, followed by family of Bagridae (29%), Cichlidae (10%), Clariidae (5%), Channidae (3%) and Pangasiidae (3%). This study shows that there is still a diversity of fish species in Pergau Lake, showing that the water and its environmental condition is very good. Satu tinjauan telah dijalankan untuk menentukan kepelbagaian ikan di Tasik Pergau, Jeli, Kelantan, Malaysia pada 2 September hingga 18 Oktober 2016. Sampel ikan telah dikumpulkan secara rawak di tujuh stesen pensampelan sekitar tasik menggunakan kaedah perangkap. Sampel yang dikumpul diawet di dalam 10% larutan formalin dan dihantar ke makmal untuk proses pengecaman. Empat belas spesis, Hemibagrus nemurus, Hampala macrolepidota, Clarias batrachus, Channa striata, Cyprinus carpio, Poropuntius smedleyi, Pangasius sp., Oreochromis niloticus, Oreochromis mossambicus, Leptobarbus hoevenii, Neolissochilus hexagonolepis, Tor tambroides, Osteochilus hasselti dan Neolissochilus soroides, terdiri daripada enam famili telah dikumpul sepanjang kajian ini dijalankan. Berdasarkan kajian, famili Cyprinidae adalah spesies yang dominan di Tasik Pergau, iaitu 50% daripada peratusan tangkapan, diikuti dengan famili Bagridae (29%), Cichilidae (10%), Clariidae (5%), Channidae (3%) dan Pangasiidae (3%). Kajian ini menunjukkan bahawa masih terdapat kepelbagaian spesies ikan di Tasik Pergau, yang menunjukkan keadaan air dan persekitaran adalah sangat baik.